2019
DOI: 10.1159/000504323
|View full text |Cite
|
Sign up to set email alerts
|

Siglec-14 Enhances NLRP3-Inflammasome Activation in Macrophages

Abstract: Pathogenic microorganisms are sensed by the inflammasome, resulting in the release of the pro-immune and proinflammatory cytokine interleukin-1β (IL-1β). In humans, the paired sialic acid-binding Ig-like lectin receptors Siglec-5 (inhibitory) and Siglec-14 (activating) have been shown to have reciprocal roles in regulating macrophage immune responses, but their interaction with IL-1β signaling and the inflammasome has not been characterized. Here we show that in response to known inflammasome activators (ATP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Among the Siglec family members, the paired receptors express extremely similar amino acid sequence of extracellular domain and comparable tissue distribution resulting in the same ligand recognition capacity whereas the diverse intracellular signalling pathways trigger the opposite effects. The paired Siglec-5 and Siglec-14 proteins, gene fusion products, are widely expressed on myeloid-derived cells residing and infiltrating human airways, however their distribution in individuals is closely related to the frequencies of wild-type and SIGLEC-14 null alleles in various populations [ 108 , 109 ]. Therefore, the expression of activating Siglec-14 receptor predominates in the European population whereas inhibitory Siglec-5 is widely expressed in Asians.…”
Section: Sialic Acids In Covs Infectionsmentioning
confidence: 99%
“…Among the Siglec family members, the paired receptors express extremely similar amino acid sequence of extracellular domain and comparable tissue distribution resulting in the same ligand recognition capacity whereas the diverse intracellular signalling pathways trigger the opposite effects. The paired Siglec-5 and Siglec-14 proteins, gene fusion products, are widely expressed on myeloid-derived cells residing and infiltrating human airways, however their distribution in individuals is closely related to the frequencies of wild-type and SIGLEC-14 null alleles in various populations [ 108 , 109 ]. Therefore, the expression of activating Siglec-14 receptor predominates in the European population whereas inhibitory Siglec-5 is widely expressed in Asians.…”
Section: Sialic Acids In Covs Infectionsmentioning
confidence: 99%
“…Most recently, it has been demonstrated that NACHT, LRR, and PYD domains-containing protein 3 (NALP3/NLRP3) inflammasome activation plays a vital role in the pathogenesis of tauopathies [ 127 ]. Importantly, SIGLEC-5 reduced NLRP3 inflammasome activation in response to Group B Streptococcus (GBS) infection [ 128 ]. Similarly, GBS β-protein bound SIGLEC-7 to inhibit NLRP3 inflammasome activation and attenuated inflammation in natural killer cells [ 129 ].…”
Section: Sialic Acid (Sia)-related Signaling: Complement Siglecs mentioning
confidence: 99%
“…Siglec-5 associates with tyrosine phosphatase SHP-1 to send an inhibitory signal upon ligation, while Siglec-14 associates with the adapter protein DAP-12 and the tyrosine kinase Syk to send an activating signal. Thus Siglec-5 binding downregulates NLRP3 inflammasome activity, while Siglec-14 binding upregulates it [8] , [16] . Importantly, there is a common polymorphism, in which Siglec-14 is replaced by a Siglec-5 like fusion protein (Siglec 14/5) signalling via the inhibitory SHP-1 pathway identically to Siglec-5 [17] .…”
Section: Potential Consequence Of Siglec 14 Null Polymorphism In Covimentioning
confidence: 98%
“…Thus, persons with Siglec-14 Null allele receive an inhibitory input to the NLRP3 inflammasome upon Siglec-5 binding while those without have a stimulatory input, greater in Siglec-14 +/+ homozygotes than heterozygotes ( Fig. 1 ) [16] , [18] . There are recognised functional consequences.…”
Section: Potential Consequence Of Siglec 14 Null Polymorphism In Covimentioning
confidence: 99%